Educating the Digital Generation - Ola Erstad (Universitetsforlaget, 2010)
The concept of a digital generation has been dominating the public discourse on the role of digital media in young people's lives. Issues concerning a digital generation is closely linked to questions about how we develop an education system that is able to face the challenges of the 21st Century. A growing field of research, inclined to raise awareness of present and future challenges for our education system, is 'media/digital literacy'. This article examines research within 'generation studies' and public constructions of young people and digital media. Further the article presents some developments within 'new literacy studies' and different aspects of 'competencies for the 21st Century'. Next, the article reflects different approaches to studying these competencies, based on different empirical data, both from my own research and that of colleagues. Towards the end the important question of inclusion and exclusion is raised. The objective is to explore some issues of importance for future development of media literacy, the educational use of digital tools and critical considerations of a digital generation. A key part of the article is the elaboration of five dimensions representing different focus areas of research on school-based studies of media literacy.